Applications of the principles organization created byjolbozzoin the competition of football in Algeria - لونيس نحاوة, (sports creativity, 2025)
Our research aims to determine the extent to which the basic principles introduced by Jules Bozzo for organizing sports competitions in football are applied. To complete our study, we selected a sample of 30 managers from regional leagues and those responsible for organization within the league. The research tool, which consisted of a questionnaire that included all the research variables, was distributed. After collecting the data and processing it statistically, we obtained results in favor of the theoretical hypothesis regarding the application of these principles in organizing sports competitions related to football.